2017
DOI: 10.1021/acsnano.7b04136
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy and Mechanistic Details of Optical Printing of Single Au and Ag Nanoparticles

Abstract: Optical printing is a powerful all-optical method that allows the incorporation of colloidal nanoparticles (NPs) onto substrates with nanometric precision. Here, we present a systematic study of the accuracy of optical printing of Au and Ag NPs, using different laser powers and wavelengths. When using light of wavelength tuned to the localized surface plasmon resonance (LSPR) of the NPs, the accuracy improves as the laser power is reduced, whereas for wavelengths off the LSPR, the accuracy is independent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 49 publications
(85 reference statements)
1
96
0
Order By: Relevance
“…In other words, the Au NPs act as antennas to receive the incident light and transfer the energy of LSPR into CdSe NBs via near‐field plasmonic wave . Therefore, the absorption of the APH@CdSe NBs was quickly increased in the range of 538–580 nm, the so‐called plasmonic resonance absorption of Au nanoparticles, except near‐band‐edge absorption at ≈710 nm. It is found that the absorption peak caused redshifts to occur with increasing sputter time.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the Au NPs act as antennas to receive the incident light and transfer the energy of LSPR into CdSe NBs via near‐field plasmonic wave . Therefore, the absorption of the APH@CdSe NBs was quickly increased in the range of 538–580 nm, the so‐called plasmonic resonance absorption of Au nanoparticles, except near‐band‐edge absorption at ≈710 nm. It is found that the absorption peak caused redshifts to occur with increasing sputter time.…”
Section: Resultsmentioning
confidence: 99%
“…The photothermal excitation of inorganic nanostructures has attracted as ignificant amount of interesti nr ecent years due to applicationsi nt he opticala blation of solid tumors, [1][2][3] the theory of hot Brownian motion, [4] the modification of metal nanostructures, [5,6] the production of contrasta gents, [7] the optical printing of materials, [8,9] the growth of semiconductor nanowires, [10][11][12][13][14] nanoscale photophoretic propulsion, [15,16] the thermala ctuation of myosin Vm otor proteins, [17] and, recently, the laser cooling of nanomaterials. [18,19] Electromagnetic theory and analyticalh eat transport solutions exist or are under development to describe many of thesea pplications.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39] Meanwhile, the physical mechanisms involved in optical printing are well understood. 35 Although potentially applicable to any colloidal NP, optical printing of colloidal NPs has been only used for metal plasmonic nanoparticles in wide range of different sizes and shapes. [40][41][42][43][44] Here, we demonstrate the size-selective optical printing of Si NPs from a polydisperse colloidal suspension produced by LAL of a Si target.…”
mentioning
confidence: 99%